Implementation Of curriculum Needs Analysis In Junior High School - Misrawita, Misrawita; Alfarisy, M. Iqbal; Alimin, Rita Amelia; Gunawan, Hendri; Efriyenti, Liza (Sekolah Tinggi Ilmu Tarbiyah (STIT) Ahlussunnah Bukittinggi, 2025)
The implementation of curriculum needs analysis at the junior high school (SMP) level is a very important step to ensure that the learning process taking place in schools is truly in line with developments in science and technology. Not only that, this analysis is also key to ensuring that learning is able to respond to the real needs of students and the community, as well as keeping up with the demands of the ever-changing world of education and industry. This research was conducted as part of these efforts, using a combination of library research and field surveys. Library research was conducted to explore various theoretical references and previous studies, while field surveys were carried out through the distribution of questionnaires and interviews with students and teachers at SMP Negeri 2 Kamang Magek. Additionally, data was collected through direct observation in the school environment and an analysis of documents related to the curriculum used. The main focus of this research is to identify the gap between the ideal curriculum and the curriculum that has been implemented in schools. In other words, this research aims to determine the extent to which the existing curriculum can meet the needs of students and the demands of the times, while also identifying priorities in curriculum development to make it more flexible, contextual, and adaptive. The results of the data analysis indicate that the current curriculum still has several weaknesses that need to be addressed. Key areas requiring attention include curriculum flexibility, the integration of character values, and the alignment of instructional materials with the characteristics and needs of students. A rigid and irrelevant curriculum can hinder effective and meaningful learning processes. Therefore, this study recommends the development of a more adaptive and contextual curriculum, as well as one that is oriented towards strengthening 21st-century skills, such as critical thinking, creativity, communication, and collaboration. Equally important, the integration of Islamic values into the curriculum needs to be continuously strengthened as part of efforts to build the character, morals, and spirituality of students. Some concrete steps recommended include adjusting the content of learning to better suit the character and potential of students, strengthening local content that can enrich the learning experience, improving teacher competence, and developing a flexible and dynamic curriculum. Thus, curriculum needs analysis is not merely an academic study but also a crucial foundation for creating a more quality, relevant, and effective education system that can better prepare the younger generation to face future challenges.